Witness [videorecording (DVD)] - Kelley, William, 1929-2003-; Wallace, Pamela; Wallace, Earl W. (Paramount, 1999)
When a young Amish woman and her son get caught up in the murder of an undercover narcotics agent, their savior turns out to be the hardened Philadelphia detective John Book, who runs head-on into the non-violent world of a Pennsylvania Amish community.